A SCIENTIFIC WORLD VIEW AND PROBLEMS OF DEVELOPMENT OF PHILOSOPHICAL SCIENCE IS IN PHILOSOPHICAL CONCEPTION OF V. VERNADSKY - Yarmolitzka, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The philosophical analysis of looks of V. Vernadsky on a scientific world view and science is conducted, becoming of this conception is traced.